DEM investigation of soil arching effect induced by vertical unloading under high geostress - Xing-Tao Lin; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Computers and Geotechnics, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Efficiently mitigating the formation of molybdate yellow phase during the nuclear waste vitrification utilizing nano zero-valent aluminum - Ze Qiu; Xing Zhao; Sinan Chen; Xiangyi Du; Yifan Li; Guangnan Luo; Mingzhang Lin (Journal of Environmental Chemical Engineering, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Biomimetic nanozyme-mediated domino catalysis for reprogramming energy metabolism to enhance ferroptosis against TNBC - Annan Liu; Lei Li; Ze Wang; Kejun Jiang; Hao Liang; Yiying Ding; Andrew K. Whittaker; Quan Lin (Chemical Engineering Journal, 2026)

Indium selenide framework constructed from supertetrahedral clusters for efficient adsorption of Cs+ and Sr2+ - Fei-Fei Wang; Yu-Hang Li; Ze-Jia Shen; Ze-Yu Wang; Lin Cheng; Shuaihua Wang; Kai-Yao Wang (Chemical Engineering Journal, 2026)

Accelerating first proton-electron transfer through nitrogen-doped defect sites for efficient H2O2 electrosynthesis - Ze Lin; Bincheng Xu; Yahui Li; Xingen Lin; Xiao Zhou; Qianyu Xu; Wenfeng Lin; Yuen Wu; Ying Wang (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Urbanization and climate extremes amplify upstream–downstream water quality disparities across Chinese urban watersheds - Lin Gao; Honghao Liu; Xiaoyu Lin; Ze Yuan; Ting Ma (Environmental Research, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

Model test study on instability of tunnel face affected by existing double circular tunnels - Xing-Tao Lin; Qi-Jia Wu; Hao Xiong; Dong Su; Ze-Yu Zhao; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Seismic behavior of novel multi-celled composite shear walls with energy-dissipating corrugated steel plates - Dai-Jiang Zhou; Xian Li; Chen-Ze Li; Zi-Lin Zhang; Xi-Guang Liu; Ming Chen (Engineering Structures, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

Physical morphology of conductive carriers shapes anaerobic biofilm development and methanogenesis - Lu Zhang; Wen He; Zu-xiang Yan; Tong-yi Yang; Lin-zhi Zhai; Xiu-jie Wang; Qian-qian Jia; Ze-chong Guo (Bioresource Technology, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

Study on Fertility and Genetic Diversity of Introduced Sugar Beet Germplasm Resource FC220 - Shi-Kun Zhang; Ya-Dan Xiao; Lin Liao; Ze-Dong Wu; Lin-Lin Sun (Sugar Tech, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Visible light driven S-type heterojunction of g-C3N4/BiOBr for efficient degradation of six high-molecular-weight pollutants with various chromophores - Yifan Wei; Jiacheng Luo; Wenjing Luo; Hongyan Zhai; Xiao Liu; Ze Xu; Qinghua Ouyang; Na Lin (Journal of Environmental Chemical Engineering, 2026)

Efficacy and mechanism of a three-dimensional electro-Fenton system combining with Fe-N-C catalyst for Microcystis aeruginosa inactivation - Ze Zhang; Yinhan Lin; Chao Xu; Jiehao Zhan; Beini Gong; Lihua Cui; Qiaoling Xu; Zhujian Huang (Journal of Environmental Chemical Engineering, 2026)

Finite-strain modelling of PVD-assisted consolidation in clayey soils using a novel elastic–viscoplastic model with destructuration based on the equivalent time concept - Peng-Lin Li; Zhen-Yu Yin; Ze-Jian Chen; Jian-Hua Yin (Geotextiles and Geomembranes, 2026)

Fluorescence spectroscopy coupled with machine learning for identification of recycled PET - Ze-Long Deng; Qing-Hua Yang; Qi-Zhi Su; Xue-Chao Song; Qin-Bao Lin (Food Packaging and Shelf Life, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Near-Surface Q-Factor Estimation Using a Non-Gaussian Energy Spectrum - Ze-lin Li; Jiang-nan Tong; Ya-nan Jiang; Tong Chen; Guo-fa Li (Applied Geophysics, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Functional characterization of a canonical C-type lectin from Mytilus coruscus: Roles in innate immunity and feeding processes - Ying-rong Jin; Chuan-yue Chen; Ze-kai Wang; Pan Qin; Zhi Liao; Xiao-lin Zhang; Xiao-jun Yan (Fish & Shellfish Immunology, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Engineering a tetrahedral framework nucleic acid-based nanomedicine for precise intracellular delivery of rapamycin to rescue senescent bone mesenchymal stem cells - Shibo Liu; Qiheng Yang; Hanghang Liu; Ze He; Xuehan Tang; Yichen Yang; Yunfeng Lin; En Luo (Chemical Engineering Journal, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Nitrogen-removal collapse and recovery: Integrative meta-omics insights into seasonal microbiome dynamics and cold-adaptive mechanisms in a full-scale activated sludge system - Limin Lin; Xinyu Zhu; Xiaoxing Lin; Ze Zhao; Hui Wang; Huizhen Yan; Feng Ju (Water Research, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Synergistic enhancement of electrochemical performances via PDA/Fe3O4 modified anodes and amino acid-mediated bioelectrocatalysis of biomineralization in marine sediment microbial fuel cells - Lin-Meng Wang; Li-Ze Huangfu; Yi Yang; Yan Chen; Yu-Bin Fu (Journal of Environmental Chemical Engineering, 2026)

Adaptive dual-mode photoelectric eutectogel interface for closed-loop human-machine interaction - Xinpeng Lv; Kai Gong; Ze Li; Zhongyuan Lin; Hongqiu Wei; Jianhui Sun; Yongjun Liu; Peng Li (Chemical Engineering Journal, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

A high-efficiency unipolar dielectric barrier discharge charger for sub-10 nm aerosol particles - Yueyang Li; Ze-Xin Chen; Runlong Cai; Michel Attoui; Yiliang Liu; Qiwen Sun; Qing Li; Lei Yao; Lin Wang (Journal of Aerosol Science, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

Pivotal effect of oxygen vacancies on S-scheme BiVO4/g-C3N4: Novel dual activation mechanistic studies in photocatalytic selective ethylbenzene oxidation under LED irradiation - Wen-Yu Luo; Ze-Lin Wang; Peng-Jiang Chao; Ying-Ying Xu; Yanfei Xu; Zhuo Li; Lin-Yu Jiao; Mingyue Ding (Chemical Engineering Journal, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Experimental study on failure mechanism of tunnel face during shield tunneling beneath existing underground rectangular structure - Xing-Tao Lin; Qi-Jia Wu; Liqiang Cao; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Hyperbranched polyamine-graft-poly(ε-caprolactone) with integrated flame retardancy, plasticization, and filler-dispersion functions toward high-performance poly(vinyl chloride) plastics - Xing-Hao Wang; Liang Yang; Jing Zhao; Ze-Zhong Lin; Dan-Dan Shi; Yu Chen; Pei-Yao Chen (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Field and laboratory investigations of the fluid in fully developed debris flows - Xiao Su; Ze-Min Xu; Yi-Xi Wen; Bin Li; Jing-Kai Meng; Lin Tian; Zi-Ming Ye; Gui-E Shi (Bulletin of Engineering Geology and the Environment, 2026)

A CFD–DEM model for simulating mechanical responses of saturated paddy soil: model development and experimental verification - He Zheng; Weiwei Duan; Ziqi Li; Yejun Zhu; Dongfang Li; Ze Liu; Wenxiang Xu; Maohua Xiao; Lin Zhu (Computers and Electronics in Agriculture, 2025)

Contrasting seasonal variations in riverine nitrogen and phosphorus concentrations in China: implications for N/P imbalances - Honghao Liu; Lin Gao; Ze Yuan; Ting Ma (Water Research, 2025)

Metamorphic conditions and cooling history of the central Himalayan eclogites: A mineralogy and zircon-titanite-rutile U Pb geochronology approach - Xin Dong; Zuo-lin Tian; Yao-ling Niu; Ze-ming Zhang (Lithos, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Enhanced electrochemical nitrate reduction: Geometrically tailored Pd/Cu electrodes for superior nitrogen selectivity - Thi Nhat-Tuyen Nguyen; Kiruthika Mariappan; Muhammad Sheraz Ahmad; Feng-Ze Tian; Ching-Wei Tung; Jenn Fang Su; Chao-Lin Liu; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2025)

Insights into the occurrence of ten bisphenol analogues in tidal flat and deepwater sediments in the Pearl River Basin - Jin-yi Sun; Ze-hua Liu; Can-yuan Lin; Jian Gong; Zhi Dang (Environmental Pollution, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

CEP78 regulates the proliferation and angiogenesis of endothelial cells by mediating microtubule stabilization via p150glued - Gang Li; Ze Zhao; Changwei Xie; Dong Lin; Wenrui Li; Xing Chen; Kaidi Ren; Yi Zhao (Journal of Molecular Histology, 2025)

Assessment of true laterites for their use as liners in karst-depression tailings impoundments - Hai-Yan Gao; Jia-Ming Zhang; Ji-Pu Chen; Lin Tian; Kun Wang; Ze-Min Xu (Bulletin of Engineering Geology and the Environment, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Polystyrene/polylactic acid microplastics impair transzonal projections and oocyte maturation via gut microbiota-mediated lipoprotein lipase inhibition - Jiacheng Zhang; Hangqi Hu; Yutian Zhu; Xiyan Xin; Yuxin Jin; Qiancheng Zhao; Haolin Zhang; Dai Heng; Ze Ma; Xicheng Chai; Ruifan Lin; Yue Zhao; et al. (Journal of Hazardous Materials, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Simultaneous detection of 12 estrogens in poultry meat and blood via ultrasonic extraction and GC–MS: Implications for emerging hormone exposure and health risk assessment - Can-yuan Lin; Ze-hua Liu; Dong-hao Luo; Xiao-zhan Wang; Jian Gong; Jin-yi Sun; Zhi Dang (Food Chemistry, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Salinity levels, trends and drivers of surface water salinization across China's river basins - Lin Gao; Ze Yuan; Xiaoteng Mao; Ting Ma (Water Research, 2025)

Characterization of solid-liquid two-phase flow in a canned-motor pump for marine vehicles based on the Euler-Lagrange method - Ze Chen; Yandong Gu; Weigang Lu; Lin Zhang; Dongdong Zhu; Zhiqiang Zhou (Ocean Engineering, 2025)

Multi-chamber bipolar membrane electrodialysis for high-purity lithium hydroxide production: A case study - Qiuyue Wang; Sheng He; Minghong Li; Benxian Yang; Lin Tian; Nicholas Ze-Xian Low (Journal of Water Process Engineering, 2025)

Unraveling the toxic trio: Combined effects of thifluzamide, enrofloxacin, and microplastics on Mytilus coruscus - Ze-Ming Zhang; Hao Liu; Hong-Lin Zuo; Yi-Nan Wang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Intelligent responsive nanosystem for precision targeting and multimodal imaging-guided high-efficient photothermal therapy against colon cancer - Lei Li; Annan Liu; Hao Liang; Xingchen Li; Maja D. Nešić; Hui Guo; Ze Wang; Quan Lin (Chemical Engineering Journal, 2025)

eDNA-Based Evaluation of the Haplotypic Diversity of Orange-Spotted Grouper (Epinephelus coioides) in Stock Enhancement Areas of Wanshan Archipelago - Chun Hui Ai; Yi Long Lin; Ming Ze Chen; Jun Hong Xia (Marine Biotechnology, 2025)

The competitive effects of crop straw return and nitrogen fertilization on soil acidification - Jia Cheng; Cheng-Ze Yang; Le Zhang; Zhuo-Jun Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Biomarkers reflecting the toxicity of neonicotinoid insecticides to the central nervous system - Yeru Yang; Xiaoyang Jiao; Fen Yao; Ze Lin; Xiaolin Guo; Meimei Wang; Qingdong Xie; Wenhua Liu; Adela Jing Li; Zhen Wang (Environmental Pollution, 2025)

Genetic Diversity Analysis of 89 Monogerm Maintainer Lines of Sugar Beet - Jing-Jing Zhao; Lin-Lin Sun; Zhi Pi; Sheng-Nan Li; Ze-Dong Wu (Sugar Tech, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Highly sensitive aggregation-induced electrochemiluminescence sensor for cadmium detection in Ganoderma lucidum - Zhi-Hong Xu; Xin Weng; Sha-Sha Wang; Ze-Hao Huang; Wen Xu; Wei Xu; Yu Lin; Hang Gao (Food Chemistry, 2025)

Heterogeneous sintering and surficial etching strategy for high-performance Cu2CoO4-SiC catalytic membranes in simultaneous multipollutant removal - Jiahao Chen; Qianxi Zhang; Bin Lin; Yarong Fang; Yiqing Zeng; Ze-Xian Low; Zhaoxiang Zhong; Weihong Xing (Chemical Engineering Journal, 2025)

Study on the Adsorption Mechanisms and Process Optimization of Different Forms of Iron Hydroxide for Low-Level Uranium-Containing Wastewater - Ze Lin; Shaokui Liu; Jiankai Wang; Jie Wang; Shaohua Hu; Jie Liu; Xuecheng Wang; Wendong Feng; Qingzhi Zhou (Water, Air, & Soil Pollution, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Cardiotoxicity of tris(2-chloroethyl) phosphate exposure: Insights into the role of oxygen sensor mediated energy metabolism remodeling - Ze Zhang; Chuer Zheng; Xinya Gu; Rifat Zubair Ahmed; Hao Yin; Jingxu Zhang; Yongfeng Lin; Jiao Luo; Yong Niu; Xiaoting Jin; Yuxin Zheng (Journal of Hazardous Materials, 2025)

Electrochemically driven inactivation of harmful cyanobacteria assisted with the visible light photocatalyst of CeO2-Fe3O4-CQDs - Ze Zhang; Hua Chai; Jiehao Zhan; Boyang Liu; Yinhan Lin; Wendi Zhang; Lihua Cui; Rongliang Qiu; Zhujian Huang (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Application of machine learning to predict the fluoride removal capability of MgO - Lin Fan; Dexi Wang; Honglei Yu; Ze Gong; Yan He; Jinyuan Guo (Journal of Environmental Chemical Engineering, 2025)

Enhancing antibiotic removal of mixed matrix membranes through electrostatic surface segregation of MIL-101(Fe) catalysts - Xia Zheng; Zhaomei Yang; Guangyong Zeng; Qingquan Lin; Xi Chen; Yuan Xiang; Yu-Hsuan Chiao; Ralph Rolly Gonzales; Ze-Xian Low; Jianquan Luo (Chemical Engineering Journal, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

Public Perception and Response to Nuclear-Contaminated Water Release in Coastal and Marine Tourism: The Case of South Korea - Ze Lin; Siyu Zhang; Wii-Joo Yhang (Coastal Management, 2025)

The volatile compound (E)-2-hexenal in wampee (Clausena lansium) represses the development of Penicillium italicum and enhances the disease resistance of postharvest citrus fruit - Ce Yang; Zizhen Lin; Ze Luo; Zhiquan Wang; Ping Liu; Rangwei Xu; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

The feasibility of batch-wise polyester degradation and recycling using recombinant Escherichia coli expressing PHB depolymerase (PhaZ ) - Yen-Chun Lin; En Ze Linda Zhong-Johnson; Anthony J. Sinskey; Si-Yu Li (Journal of Environmental Management, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Uncovering the key lncRNAs in regulating cadmium accumulation and translocation in sweet sorghum - Kangqi Lin; Ze Yi; Sulian Lv; Bo Zhang; Zijin Guo; Yinxin Li (Planta, 2025)

Enhanced spectral reconstruction of ultrafast spatiotemporal encoded 2D NMR spectroscopy - Hong Li; Yida Chen; Ze Fang; Yulan Lin; Lucio Frydman; Yu Yang; Zhong Chen (Analytica Chimica Acta, 2025)

Oriented regulation of earthworm production and vermicompost quality by carbon bioavailability management - Jiacong Lin; Dingmei Wang; Lingwei Kong; Liwen Mai; Shiliang Peng; Qinfen Li; Yupeng Wu; Jing Yuan; Guoxue Li; Ze Meng (Science of The Total Environment, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

Defect engineering induced high metal loading Co-single-atom catalyst on carbon dots for efficient H2O2 electrosynthesis - Ze Lin; Yahui Li; Ruilong Li; Xingen Lin; Bincheng Xu; Zhixuan Chen; Yuen Wu; Ying Wang (Chemical Engineering Journal, 2024)

Microbiota succession, species interactions, and metabolic functions during autotrophic biofloc formation in zero-water-exchange shrimp farming without organic carbon supplements - Yuchun Li; Fei Huang; Sheng Dong; Lingcheng Liu; Langli Lin; Ze Li; Yihong Zheng; Zhangli Hu (Bioresource Technology, 2024)

Activation of Inflammasomes and Relevant Modulators for the Treatment of Microglia-mediated Neuroinflammation in Ischemic Stroke - Ze-Jie Zeng; Xiaobing Lin; Liu Yang; Yi Li; Wen Gao (Molecular Neurobiology, 2024)

PFOS impairs cardiac function and energy metabolism under high-fat diet: Insights into role of circulating macrophage emphasized by exposure distribution - Ze Zhang; Hao Yin; Chuer Zheng; Zhenhua Yu; Rifat Zubair Ahmed; Yong Niu; Chengying Zhou; Jian Ding; Huan Lin; Yongfeng Lin; Yuxin Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Using magnesium hydride as the future dual-mode propellant for spacecraft: A simulation investigation - Xi Lin; Ze Zhang; Lianshen Bian; Longfei Shao; Yinglong Kang; Keming Zhang; Jianxin Zou (Chemical Engineering Journal, 2024)

High mobility emissive BN-Embedded Dinaphthalenyl anthracene for organic light emitting transistors - Ze-Wei Lin; Pu Wang; Sheng-Hong Zhao; Yun-Tao Ding; Huanli Dong; Hao-Li Zhang (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Rnai-based functional analysis of bursicon genes related to cuticle pigmentation in a ladybird beetle - Lan-Lan Liao; Wen-Ze Li; Lin Jin; Guo-Qing Li (Journal of Insect Physiology, 2024)

The effects of dietary supplementation of ginseng stem and leaf saponins on the antioxidant capacity, immune response, and disease resistance of crucian carp, Carassius auratus - Ying-da Wang; Xin Meng; Yong-chao Guan; Ze-lin Zhao; Luo-tao Tao; Jin-shuo Gong; Xin-lan Liu; Yan Zhao; Xiao-feng Shan (Fish Physiology and Biochemistry, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Solidago canadensis enhances its invasion by modulating prokaryotic communities in the bulk soil - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Dao-Lin Du; Ze-Yu Li; Xin-Yu Wang (International Biodeterioration & Biodegradation, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Behavioral events and functional analysis of bursicon signal during adult eclosion in the 28-spotted larger potato ladybird - Wen-Ze Li; Yi-Kuan Wu; Yu-Xing Zhang; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Identification of Epicoccum latusicollum causing leaf spot disease on Bletilla striata in China - Jingyi Guo; Xueming Huang; Siyu Lin; Ze Liu; Hanyi Wang; Qi Gao; Hao Zhou (Crop Protection, 2024)

QseC regulates chemotaxis, biofilm formation, motility, and virulence in Aeromonas veronii TH0426 - Luo-tao Tao; Lu Wang; Jing Xiong; Liang Chen; Ze-lin Zhao; Dong-xing Zhang; Lei Zhang; Wu-wen Sun; Xiao-feng Shan (Aquaculture, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Structure and dynamics of microbial communities associated with the resurrection plant Boea hygrometrica in response to drought stress - Run-Ze Sun; Yuan-Yuan Wang; Xiao-Qiang Liu; Zhao-Lin Yang; Xin Deng (Planta, 2024)

The Association Between Dietary Magnesium Intake with Chronic Obstructive Pulmonary Disease and Lung Function in US Population: a Cross-sectional Study - Zhi-Feng Lin; Hua-Wei Lin; Wan-Zhe Liao; Ze-Min Huang; Xiao-Yue Liao; Yi-Yao Wang; Xu-Guang Guo (Biological Trace Element Research, 2024)

Review of energy supply techniques for ice in-situ thermal mining in lunar permanently shadowed regions - Yan Zhang; Yun-ze Li; Jia-lin Zhang (Advances in Space Research, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Observation of an acoustic topological Euler insulator with meronic waves - Bin Jiang; Adrien Bouhon; Shi-Qiao Wu; Ze-Lin Kong; Zhi-Kang Lin; Robert-Jan Slager; Jian-Hua Jiang (Science Bulletin, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

A modified drag coefficient model for calculating the terminal settling velocity and horizontal diffusion distance of irregular plume particles in deep-sea mining - Ze-lin Liu; Qiu-hua Rao; Wei Yi; Wei Huang (Environmental Science and Pollution Research, 2024)

SCREENES: Enhancing non-uniform sampling reconstruction for symmetrical NMR spectroscopy - Ze Fang; Bo Chen; Chengda Huang; Yifei Yuan; Yao Luo; Liubin Wu; Yida Chen; Yuqing Huang; Yu Yang; Enping Lin; Zhong Chen (Analytica Chimica Acta, 2024)

A concise review of resource requirements for future space exploration - Jia-Lin Zhang; Yun-Ze Li; Yan Zhang (Advances in Space Research, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Pruritic Erythema in a Child with Undifferentiated Connective Tissue Disease - Qi-Hao Yao; Xiu-Jiao Xia; Hui-Lin Zhi; Ze-Hu Liu (Mycopathologia, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Establishment of a TaqMan probe‐based qPCR assay for detecting microsporidia Enterospora epinepheli in grouper - Quan‐lin Liu; Yuan Wang; Jie Chen; Guo‐qing Pan; Yan‐Feng Yue; Ze‐Yang Zhou; Wen‐hong Fang (Journal of Fish Diseases, 2024)
Enterospora epinepheli is an intranuclear microsporidian parasite causing serious emaciative disease in hatchery‐bred juvenile groupers ( Epinephelus spp.). Rapid and sensitive detection is urgently needed as its chronic infection tends to cause emaciation as well as white faeces syndrome and results in fry mortality. This study established a TaqMan probe‐based real‐time quantitative PCR assays targeting the small subunit rRNA (SSU) gene of E. epinepheli. The relationship between the standard curve of cycle threshold (Ct) and the logarithmic starting quantity (SQ) was determined as Ct = −3.177 lg (SQ) + 38.397. The correlation coefficient ( R 2 ) was 0.999, and the amplification efficiency was 106.4%. The detection limit of the TaqMan probe‐based qPCR assay was 1.0 × 10 1 copies/μL and that is 100 times sensitive than the traditional PCR method. There is no cross‐reaction with other aquatic microsporidia such as Ecytonucleospora hepatopenaei , Nucleospora hippocampi , Potaspora sp., Ameson portunus. The intra‐assay and inter‐assay showed great repeatability and reproducibility. In addition, the test of clinical samples showed that this assay effectively detected E. epinepheli in the grouper's intestine tissue. The established TaqMan qPCR assays will be a valuable diagnostic tool for the epidemiological investigation as well as prevention and control of E. epinepheli .

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Preparation of CPVC-based activated carbon spheres and insight into the adsorption-desorption performance for typical volatile organic compounds - Ning Dong; Ze Wang; Jun Wang; Wenli Song; Lin Du; Xiangyu Gu; Songgeng Li (Environmental Pollution, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Ambient PM2.5 components and prevalence of chronic kidney disease: a nationwide cross-sectional survey in China - Chao Yang; Wanzhou Wang; Fulin Wang; Yueyao Wang; Feifei Zhang; Ze Liang; Chenyu Liang; Jinwei Wang; Lin Ma; Pengfei Li; Shuangcheng Li; Luxia Zhang (Environmental Geochemistry and Health, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Crucial physicochemical factors mediating mitochondrial toxicity of nanoparticles at noncytotoxic concentration - Ze Zhang; Gan Miao; Lin Lu; Hao Yin; Yingzhu Wang; Baoqiang Wang; Ruonan Pan; Chuer Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Generation and origin of persistent high excess pore water pressure in debris flows - Zi-Ming Ye; Ze-Min Xu; Bin Li; Xiao Su; Gui-E Shi; Jing-Kai Meng; Lin Tian (Geomorphology, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Deciphering the bioavailability of dissolved organic matter in thermophilic compost and vermicompost at the molecular level - Dingmei Wang; Liwen Mai; Zhen Yu; Kongtan Wang; Ze Meng; Xiongfei Wang; Qinfen Li; Jiacong Lin; Dongming Wu (Bioresource Technology, 2024)

Young people exposure to antibiotics: Implication for health risk and the impact from eating habits of takeaway food - Hao Yang; Dong-Min Ye; Ze-Zhao Lin; Xiao-Ya Lin; Jia-Jun Yuan; Ying Guo (Science of The Total Environment, 2023)

Comprehensive profiling and risk assessment of antibiotic resistance genes in a drinking water watershed by integrated analysis of air-water-soil - Zhen-Chao Zhou; Xin-Yi Shuai; Ze-Jun Lin; Ji Zheng; Hong Chen (Journal of Environmental Management, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Reexamining the Causes and Effects of Cholesterol Deposition in the Brains of Patients with Alzheimer’s Disease - Ze-Lin Hu; Yang-Qi Yuan; Zhen Tong; Mei-Qing Liao; Shun-Ling Yuan; Ye Jian; Jia-Lun Yang; Wen-Feng Liu (Molecular Neurobiology, 2023)

Flood risk assessment of check dams in the Wangmaogou watershed on the Loess Plateau of China - Ze-chao Gao; Peng Shi; Zhan-bin Li; Peng Li; Lu-lu Bai; Yi Jia; Lin Cui (Journal of Mountain Science, 2023)

A short review on environmental distribution and toxicity of the environmentally persistent free radicals - Jing-Feng Yi; Ze-Zhao Lin; Xing Li; Yue-Qiao Zhou; Ying Guo (Chemosphere, 2023)

Hcp1 regulates flagella of Aeromonas veronii TH0426 to reduce virulence - Ying-da Wang; Jin-shuo Gong; Yong-chao Guan; Ze-lin Zhao; Ya-nan Cai; Xiao-feng Shan (Aquaculture, 2023)

Distinct patterns of the soil and phyllosphere antibiotic resistome in natural forest ecosystems under an altitudinal gradient - Shu-Yi-Dan Zhou; Fu-Yi Huang; Wei Su; Zhiyang Lie; Yue Liu; Chenshuo Lin; Kai Yang; Ze Meng; Zhanfeng Liu; Roy Neilson; Jian-Qiang Su; Juxiu Liu (Science of The Total Environment, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Effects of light intensity and salinity on formation and performance of microalgal-bacterial granular sludge - Ze Li; Ziyan Wang; Si Cai; Langli Lin; Guanqin Huang; Zhangli Hu; Wenbiao Jin; Yihong Zheng (Bioresource Technology, 2023)

Successful Treatment of Diffuse Pustular Inflammatory Tinea Capitis in the Elderly with Repeated Debridement, Oral Terbinafine and Short-Course Steroids - Yuan Xu; Xiu-Jiao Xia; Hui-Lin Zhi; Ze-Hu Liu (Mycopathologia, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

Drynaria Naringin alleviated mechanical stress deficiency-caused bone loss deterioration via Rspo1/Lgr4-mediated Wnt/β-catenin signalling pathway - Gui-Xun Shi; Wei-Dong Sun; Zeng-Huan Chen; Chuan-Jun Yang; Wang-Lin Luo; Dan-Feng Wang; Ze-Zhu Zhou (In Vitro Cellular & Developmental Biology - Animal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

An extracellular matrix-inspired self-healing composite hydrogel for enhanced platelet-rich plasma-mediated chronic diabetic wound treatment - Ya Zhang; Zi-Li Wang; Ze-Peng Deng; Zi-Lin Wang; Fei Song; Li-Li Zhu (Carbohydrate Polymers, 2023)

Enhancing Solubility and Dissolution Behavior of Finasteride Using Solid Dispersion Technique by Carrier Screening and the New Preparation Instrument - Lin-Jie Wang; Yi-Chao Su; Peng-Tu Zhang; Xin Ji; Jin-Ze Du (Journal of Pharmaceutical Innovation, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Yeast biomass ornamented macro-hierarchical chitin nanofiber aerogel for enhanced adsorption of cadmium(II) ions - Iqra Shahzadi; Yang Wu; Heng Lin; Jing Huang; Ze Zhao; Chaoji Chen; Xiaowen Shi; Hongbing Deng (Journal of Hazardous Materials, 2023)

Characteristics of spatial and temporal carbon emissions from different land uses in Shanxi section of the Yellow River, China - Lin Zhao; Meng-na Chen; Chuan-hao Yang; Run-ze Zhang; Qi-peng Zhang; Qian Wang (Environment, Development and Sustainability, 2023)

Fine-tuning immunity against cancer: the emergence of engineered commensal microbiota - Shi-Jun He; Fan Yang; Jian-Ping Zuo; Ze-Min Lin (Science Bulletin, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Understanding the spatial relationships and drivers of ecosystem service supply-demand mismatches towards spatially-targeted management of social-ecological system - Jiashu Shen; Shuangcheng Li; Huan Wang; Shuyao Wu; Ze Liang; Yatong Zhang; Feili Wei; Shuang Li; Lin Ma; Yueyao Wang; Laibao Liu; Yajuan Zhang (Journal of Cleaner Production, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Crowding-out strategy to enhance energetics of 3-nitro-1,2,4-triazol-5-one based E-MOFs at the molecular level through adjusting pH - Xiaopeng Zhang; Tianyang Hou; Yige Wu; Ze Xu; Qiuhan Lin; Pengcheng Wang; Yuangang Xu; Ming Lu (Chemical Engineering Journal, 2023)

Responsive Transcriptome Analysis of Senecio vulgaris L. Under Different Drought Stresses - Hongbo Pang; Yuanming Wu; Yueying Li; Longkun Wu; Ze Wang; Lin Chang; Hongxin Liu; Qiang Chen (Journal of Plant Growth Regulation, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

A new anthraquinone from mangrove endophytic fungus Aspergillus sp. 16-5C - Ze’en Xiao; Shao’e Lin; Zhigang She; Yongjun Lu; Zhen Tan; Yonghong Liu (Natural Product Research, 2023)

Identification and degradation of structural extracellular polymeric substances in waste activated sludge via a polygalacturonate-degrading consortium - Zhi-Yi Hu; Yi-Peng Lin; Qing-Ting Wang; Yi-Xin Zhang; Jie Tang; Si-Di Hong; Kun Dai; Shuai Wang; Yong-Ze Lu; Mark C.M. van Loosdrecht; Jianrong Wu; Raymond Jianxiong Zeng; et al. (Water Research, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Lycopene ameliorates atrazine-induced spatial learning and memory impairments by inhibiting ferroptosis in the hippocampus of mice - Shi-Yong Zhu; Jun-Ze Jiang; Jia Lin; Lin Liu; Jian-Ying Guo; Jin-Long Li (Food and Chemical Toxicology, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Regional urbanicity levels modify the association between ambient air pollution and prevalence of obesity: A nationwide cross-sectional survey - Chao Yang; Wanzhou Wang; Ze Liang; Yueyao Wang; Rui Chen; Chenyu Liang; Fulin Wang; Pengfei Li; Lin Ma; Feili Wei; Shuangcheng Li; Luxia Zhang (Environmental Pollution, 2023)

Hydrogen bonding donor/acceptor active sites exposed on imide-functionalized carbon dots aid in enhancing arsenic adsorption performance - Ze Lin; Limin Jin; Yanbiao Liu; Ying Wang (Chemical Engineering Journal, 2023)

Shrub encroachment increases soil erosion risk in hillside alpine meadows of the Qinghai-Tibetan Plateau, NW China - Yi-Fan Liu; Hui Fang; Ze Huang; Pedro A.M. Leite; Yu Liu; Manuel López-Vicente; Jingxue Zhao; Zhi-Hua Shi; Gao-Lin Wu (CATENA, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Ongoings in the apple watercore: First evidence from proteomic and metabolomic analysis - Mingyi Yang; Qianwei Lin; Zisheng Luo; Zhaojun Ban; Xihong Li; Russel J. Reiter; Shuang Zhang; Lei Wang; Ze Liang; Ming Qi; Li Li (Food Chemistry, 2023)

Synergistically enhanced structural, thermal and interfacial stability of K0.45MnO2 via tailoring the local structure for high-energy and high-power potassium-ion batteries - Yan Huang; Xinyuan Zhang; Hezhe Lin; Zhixuan Wei; Yi Zeng; Xin Ge; Wei Zhang; Xiaoqi Wang; Xu Jin; Ze Xiang Shen; Fei Du (Chemical Engineering Journal, 2023)

Somatostatin-Positive Neurons in the Rostral Zona Incerta Modulate Innate Fear-Induced Defensive Response in Mice - Shan Lin; Meng-Yue Zhu; Meng-Yu Tang; Mi Wang; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Dan Yang; Jiadong Chen; Xiao-Ming Li (Neuroscience Bulletin, 2023)
Defensive behaviors induced by innate fear or Pavlovian fear conditioning are crucial for animals to avoid threats and ensure survival. The zona incerta (ZI) has been demonstrated to play important roles in fear learning and fear memory, as well as modulating auditory-induced innate defensive behavior. However, whether the neuronal subtypes in the ZI and specific circuits can mediate the innate fear response is largely unknown. Here, we found that somatostatin (SST)-positive neurons in the rostral ZI of mice were activated by a visual innate fear stimulus. Optogenetic inhibition of SST-positive neurons in the rostral ZI resulted in reduced flight responses to an overhead looming stimulus. Optogenetic activation of SST-positive neurons in the rostral ZI induced fear-like defensive behavior including increased immobility and bradycardia. In addition, we demonstrated that manipulation of the GABAergic projections from SST-positive neurons in the rostral ZI to the downstream nucleus reuniens (Re) mediated fear-like defensive behavior. Retrograde trans-synaptic tracing also revealed looming stimulus-activated neurons in the superior colliculus (SC) that projected to the Re-projecting SST-positive neurons in the rostral ZI (SC-ZIr SST -Re pathway). Together, our study elucidates the function of SST-positive neurons in the rostral ZI and the SC-ZIr SST -Re tri-synaptic circuit in mediating the innate fear response.

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Damage stratigraphy as a controlling mechanism of earthquakes distribution and fault patterns - Zonghu Liao; Lin Zhang; Huayao Zou; Fang Hao; Ze'ev Reches (Tectonophysics, 2023)

Disruption of tetrahydrobiopterin (BH4) biosynthesis pathway affects cuticle pigmentation in Henosepilachna vigintioctopunctata - Long-Ji Ze; Ping Xu; Jian-Jian Wu; Lin Jin; Ahmad Ali Anjum; Guo-Qing Li (Journal of Insect Physiology, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Cation-doped V2O5 microsphere as a bidirectional catalyst to activate sulfur redox reactions for lithium-sulfur batteries - Fan-Jun Liu; Wen-Lin Luo; Ze Zhang; Ji Yu; Jian-Xin Cai; Zhen-Yu Yang (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Effect of Zn2+-Cu2+ combined heavy metal on mechanical properties and microstructure of clayey soil - Qiang Ma; Nian-ze Wu; Heng-lin Xiao; Wen-tao Li; Jun-chen Xiang (Journal of Mountain Science, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Research of Intelligent Logistics and High-Quality Economy Development for Yangtze River Cold Chain Shipping Based on Carbon Neutrality - Ruiqi Xiao; Lin Pan; Hanbin Xiao; Han Xiao; Ze Zhu (Journal of Marine Science and Engineering, 2022)
The current status of intelligent logistics and cold chain shipping research is a hot topic worldwide. Meanwhile, the study of regional logistics and regional economy, shipping logistics and regional economic theory and application methods, and the empirical analysis of the correlation between the Yangtze River shipping and the Yangtze River shipping economy have attracted a lot of attention. This research has revealed that the Internet of Things of Yangtze River shipping has a great impact on the Yangtze River and the importance of inland river economic development. This study presents the empirical analysis on the correlation between shipping logistics and the inland river economy, starting from qualitative and quantitative aspects, and taking Yangtze River shipping as the representative. The proposed mathematical models and qualitative data analysis are made on the relevant effects of intelligent logistics and cold chain shipping on an inland river economy including its impact on the industrial layout, international trade, and urbanization. The research results provide administrative decisions or guidance values for the economic development of inland river ports in the Yangtze River.

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Stability and deformation of Xiaozhuang landslide: A large-scale creeping landslide in Gansu, China - Ze-lin Zhang; Tao Wang (Journal of Mountain Science, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Highly selective monoclonal antibody-based lateral flow immunoassay for visual and sensitive determination of conazole fungicides propiconazole in vegetables - Ze-Ke Xu; Jing-Nan Meng; Yi Lei; Xing-Xing Yang; Yi-Yong Yan; Hai-Hong Liu; Hong-Tao Lei; Ting-Cai Wang; Xing Shen; Zhen-Lin Xu (Food Additives & Contaminants: Part A, 2022)

Adaptations of Plutella xylostella adult females and larvae to waxy host plants - Jing-Yun Zhu; Zhong-Wen Xiang; Shi-Ze Zhang; Lin-Nan Wu; Tong-Xian Liu (Journal of Pest Science, 2022)

Characterization on the P-associated and agronomic traits as well as associated molecular processes in wheat under Pi deprivation condition - Ying-Jia Zhao; Xin-Yang Bai; Rui-Ze Lin; Fang-fang Li; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Study on the Quantitative Relationship Among Canopy Hyperspectral Reflectance, Vegetation Index and Cotton Leaf Nitrogen Content - Caixia Yin; Jiao Lin; Lulu Ma; Ze Zhang; Tongyu Hou; Lifu Zhang; Xin Lv (Journal of the Indian Society of Remote Sensing, 2021)
Study the response mechanism of Canopy spectral reflectance (CSR) to cotton nitrogen fertilizer, propose the sensitive band and center wavelength of cotton leaf nitrogen content (LNC), and compare the response characteristics of various vegetation indexes to LNC, propose a vegetation index that responds well to LNC and construct estimating model. This experiment sets five nitrogen fertilizer levels, namely N 0 (control), N 120 (120 kg/hm 2 ), N 240 (240 kg/hm 2 ), N 360 (360 kg/hm 2 ), N 480 (480 kg/hm 2 ). Among them, referring to the conventional nitrogen fertilizer is applied by local farmers (N 330 , 330 kg/hm 2 ). The results showed the following: (1) Visible light and near-infrared (NIR) can be used as two large ranges for precise monitoring of nitrogen, especially the CSR in the NIR range differs significantly under different nitrogen fertilizers. In the early stage of cotton growth, the CSR decreased with the nitrogen application rate increase, in a suitable nitrogen environment (360 kg/hm 2 ), and beyond N 360 , vice versa. In the later growth period, the CSR increases with the increase in nitrogen fertilizer. This trend is most evident in the short-wave NIR regions;(2) the range of 690–709 nm, 717–753 nm, and 940–958, which can be remote sensed by the spectral reflectance when cotton is affected in poor or rich nitrogen. The center wavelength corresponding to the nitrogen-sensitive band, respectively, are 697 nm, 735 nm, 953 nm, the band width can maintain 5–15 nm, generally not more than 20 nm;(3) compared with the ratio vegetation index, difference vegetation index, and normalized vegetation index, the combined vegetation index of more than two bands has a better effect on cotton LNC monitoring, of which the index (R 560 −R 670 )/(R 560 + R 670 −R 450 ), (R 700 −1.7 × R 670 + 0.7 × R 450 )/(R 700 + 2.3 × R 670 −1.3 × R 450 ) are significantly related to LNC in this papers, and the correlation coefficients can reach, respectively, 0.935 * and 0.936 * . These findings help to estimate the model of LNC. The model is as follows: Y = 19.883 × x + 42.285, where x refers to the combined vegetation index (R 700 −1.7 × R 670 + 0.7 × R 450 )/(R 700 + 2.3 × R 670 −1.3 × R 450 ), Y is LNC, but the model accuracy will be affected in the crop different phenological stage, and the model has the highest monitoring accuracy during the bud period.

Gas-phase isopropanol degradation by nonthermal plasma combined with Mn-Cu/-Al2O3 - Ken-Lin Chang; Yu-Chieh Lin; Ming-Ze Qiu; Chun-Wei Tu; Chih-Ping Chang; Jhong-Lin Wu; Yung-Chang Lin; Chien-Kuei Chang (Environmental Science and Pollution Research, 2021)

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Inversion analysis of the shear strength parameters for a high loess slope in the limit state - Xiao-yan Lin; Lin-fan Zhang; Ze Yang; Ping Li; Tong-lu Li (Journal of Mountain Science, 2021)

Numerical analysis of loess and weak intercalated layer failure behavior under direct shearing and cyclic loading - Ze-lin Zhang; Tao Wang (Journal of Mountain Science, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Expression Patterns of Inducible Cre Recombinase Driven by Differential Astrocyte-Specific Promoters in Transgenic Mouse Lines - Neng-Yuan Hu; Ya-Ting Chen; Qian Wang; Wei Jie; Yi-Si Liu; Qiang-Long You; Ze-Lin Li; Xiao-Wen Li; Sophie Reibel; Frank W. Pfrieger; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Distribution and features of landslides in the Tianshui Basin, Northwest China - Ze-lin Zhang; Tao Wang; Shu-ren Wu (Journal of Mountain Science, 2020)

Inhibitory effect of Fungastop and Bion against carrot soft rot caused by Sclerotinia sclerotiorum - Seyedmohammadreza Ojaghian; Ling Wang; Jing-Ze Zhang; Guan-Lin Xie (Phytoparasitica, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Antimicrobial and cytotoxic juglones from the immature exocarps of Juglans mandshurica - Qin Yang; Qing-Shou Yao; Yi Kuang; Yue-Zhi Zhang; Ling-Ling Feng; Lu Zhang; Lin Guo; Ze-Ping Xie; Shu-Min Zhang (Natural Product Research, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Evaluation of the impact of karst depression-type impoundments on the underlying karst water systems in the Gejiu mining district, southern Yunnan, China - Hai-Yan Gao; Ze-Min Xu; Kun Wang; Zhe Ren; Kui Yang; Yong-Jun Tang; Lin Tian; Ji-Pu Chen (Bulletin of Engineering Geology and the Environment, 2019)

Warming changes soil N and P supplies in model tropical forests - Zhiyang Lie; Wei Lin; Wenjuan Huang; Xiong Fang; Chumin Huang; Ting Wu; Guowei Chu; Shizhong Liu; Ze Meng; Guoyi Zhou; Juxiu Liu (Biology and Fertility of Soils, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

A Numerical Investigation on the Flooding Process of Multiple Compartments Based on the Volume of Fluid Method - XinLong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Ze Li; Fei Liu (Journal of Marine Science and Engineering, 2019)
A detailed description of the flooding process is crucial to analyze the complex hydrodynamic behaviors and enhance the survivability of the damaged ship. In this paper, through establishing three typical damage scenarios with various locations, the commercial software CD Adapco STAR-CCM+ based on the Reynolds-Averaged Navier-Stokes (RANS) solver is applied to simulate the flooding process involving multiple compartments. The basic computational fluid dynamics (CFD) models and specific simulation settings are elaborated. The volume of fluid (VOF) method combined with the user defined field function is developed to distribute the initial free surface. The captured flooding process indicates that the air compression due to the restricted ventilation decreases the flooding amount. The obtained flooding time can provide necessary data to support for appropriate rescue management and evacuation options.

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Winter chemical partitioning of metals bound to atmospheric fine particles in Dongguan, China, and its health risk assessment - Lin Huang; Yun-He Bai; Rui-Yue Ma; Ze-Ming Zhuo; Ling Chen (Environmental Science and Pollution Research, 2019)

The effects of different pharmacological agent treatments on ROS accumulation and functional protein activities in wheat endosperm PCD - Ze Lin; Yuanhong Qi; Dongcheng Liu; Fangfang Mao; Xiangyi Deng; Jiwei Li; Fangzhu Mei; Zhuqing Zhou (Acta Physiologiae Plantarum, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

Impacts of small woody debris on slurrying, persistence, and propagation in a low-gradient channel of the Dongyuege debris flow in Nu River, Southwest China - Yong-Jun Tang; Ze-Min Xu; Tai-Qiang Yang; Zhen-Hua Zhou; Kun Wang; Zhe Ren; Kui Yang; Lin Tian (Landslides, 2018)

Methyl jasmonate and salicylic acid elicitation increase content and yield of chlorogenic acid and its derivatives in Gardenia jasminoides cell suspension cultures - Ze-Bo Liu; Ji-Guang Chen; Zhong-Ping Yin; Xin-Chen Shangguan; Da-Yong Peng; Tao Lu; Ping Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Time evolution and spatial accumulation of progressive failure for Xinhua slope in the Dagangshan reservoir, Southwest China - Ming-liang Chen; Peng-fei Lv; Shi-lin Zhang; Xing-ze Chen; Jia-wen Zhou (Landslides, 2018)

Fast trace determination of nine odorant and estrogenic chloro- and bromo-phenolic compounds in real water samples through automated solid-phase extraction coupled with liquid chromatography tandem mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-xian Lian; Chuang-tao Yang; Qing Lin; Hua Yin; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Early Jurassic metamorphism of the eastern segment of the Lhasa terrane in South Tibet and its tectonic significance - Zhi-Jia Chen; Zuo-Lin Tian; Ze-Ming Zhang; Xin Dong (International Geology Review, 2017)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

Simultaneous determination of estrogenic odorant alkylphenols, chlorophenols, and their derivatives in water using online headspace solid phase microextraction coupled with gas chromatography-mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-Xian Lian; Chuangtao Yang; Qing Lin; Hua Yin; Zhi Dang (Environmental Science and Pollution Research, 2016)

Early detection of white mold caused by Sclerotinia sclerotiorum in potato fields using real-time PCR - Mohammad Reza Ojaghian; Jing-Ze Zhang; Fan Zhang; Wen Qiu; Xiao-Lin Li; Guan-Lin Xie; Shui-Jin Zhu (Mycological Progress, 2016)

Interleukin-17A Acts to Maintain Neuropathic Pain Through Activation of CaMKII/CREB Signaling in Spinal Neurons - Cheng-ye Yao; Ze-lin Weng; Jian-cheng Zhang; Tao Feng; Yun Lin; Shanglong Yao (Molecular Neurobiology, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Occurrence, spatial distribution, sources, and risks of polychlorinated biphenyls and heavy metals in surface sediments from a large eutrophic Chinese lake (Lake Chaohu) - Wei He; Ze-Lin Bai; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Sven Erik Jørgensen; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

CarHSFB2, a Class B Heat Shock Transcription Factor, Is Involved in Different Developmental Processes and Various Stress Responses in Chickpea (Cicer Arietinum L.) - Hao Ma; Chuntao Wang; Bin Yang; Huiying Cheng; Ze Wang; Abudoukeyumu Mijiti; Cai Ren; Guanghang Qu; Hua Zhang; Lin Ma (Plant Molecular Biology Reporter, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

The NPR1 homolog GhNPR1 plays an important role in the defense response of Gladiolus hybridus - Xionghui Zhong; Lin Xi; Qinglong Lian; Xian Luo; Ze Wu; Shanshan Seng; Xue Yuan; Mingfang Yi (Plant Cell Reports, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Physical regulation of stem cells differentiation into teno-lineage: current strategies and future direction - Jia Lin Chen; Wei Zhang; Ze Yu Liu; Boon Chin Heng; Hong Wei Ouyang; Xue Song Dai (Cell and Tissue Research, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Isolation and characterization of 25 polymorphic microsatellite loci from the Hynobius maoershanensis (Caudata: Hynobiidae) - Bing-jie Lin; Hua-yuan Huang; Zhong-hui Wei; Ze-ning Chen; Shao-neng Wang; Zheng-jun Wu (Conservation Genetics Resources, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Enzymatic Production of Biodiesel from Millettia pinnata Seed Oil in Ionic Liquids - Ze-Lin Huang; Tao-Xiang Yang; Jian-Zi Huang; Zhen Yang (BioEnergy Research, 2014)

2.5D induced polarization forward modeling using the adaptive finite-element method - Yi-Xin Ye; Yu-Guo Li; Ju-Zhi Deng; Ze-Lin Li (Applied Geophysics, 2014)

Lung Cancer Stem Cells and Implications for Future Therapeutics - Jing Wang; Ze-hong Li; James White; Lin-bo Zhang (Cell Biochemistry and Biophysics, 2014)

The influence of background waves on internal solitary waves after the transit of Typhoon Neast in the northern South China Sea - Feilong Lin; Yijun Hou; Ze Liu; Po Hu; Yong Fang; Yongliang Duan (Acta Oceanologica Sinica, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Xylanthraquinone, a new anthraquinone from the fungus Xylaria sp. 2508 from the South China Sea - Xishan Huang; Xuefeng Sun; Shao'e Lin; Ze'en Xiao; Hanxiang Li; Ding Bo; Zhigang She (Natural Product Research, 2014)

Potential hydraulic efficiency in angiosperm trees increases with growth‐site temperature but has no trade‐off with mechanical strength - Shi‐Bao Zhang; Kun‐Fang Cao; Ze‐Xin Fan; Jiao‐Lin Zhang (Global Ecology and Biogeography, 2013)
Aim Xylem structures are closely related to a tree's hydraulic efficiency and mechanical stability, both of which affect the life history and ecological strategy of a species. Although mechanical strength and hydraulic capacity can be shaped by the environment, no such associations between hydraulic efficiency and climatic variables have been reported across a wide range of tree species. Location Y unnan, south‐west C hina. Methods We compiled a data set for vessel density, vessel diameter ( D ), potential hydraulic conductivity ( K p ), wood density ( WD ), modulus of rupture ( MOR ) and modulus of elasticity ( MOE ) from 316 angiosperm tree species. Our objective was to examine the correlations among xylem traits and climatic variables. We hypothesized that both hydraulic efficiency and mechanical strength would vary along climatic gradients, but that a trade‐off would occur between them. Results All xylem traits varied significantly across species, but the magnitudes of variation were greater for vessel traits than for mechanical properties. Values for K p and D increased with mean annual temperature ( MAT ) in both evergreen and deciduous trees, but they were significantly correlated with aridity index ( AI ) in evergreen species only. Both WD and MOR were significantly correlated with MAT only in evergreen trees. MOR decreased with increasing AI in the evergreens, but not in deciduous trees. These findings indicated that xylem development in evergreens is more sensitive to environmental changes than in deciduous trees. However, stem hydraulic traits are independent of mechanical properties. Main conclusions Consistent with our hypothesis, both hydraulic efficiency and mechanical strength of angiosperm trees are influenced by the environment, with temperature having a more important effect on hydraulic efficiency than precipitation. However, no trade‐off exists between efficiency and strength. This absence of a link is explained because angiosperms have xylem tissue that specifically functions in either mechanical strength or water transport.

Development of SNP markers associated with defense mechanism of sea cucumber, Apostichopus japonicas - Lin-lin Gao; Meng Chen; Ya-Qing Chang; Nan-Jing Ji; Cheng-Ze Li (Conservation Genetics Resources, 2013)

Polyphyly of the Padus group of Prunus (Rosaceae) and the evolution of biogeographic disjunctions between eastern Asia and eastern North America - Xiao-Lin Liu; Jun Wen; Ze-Long Nie; Gabriel Johnson; Zong-Suo Liang; Zhao-Yang Chang (Journal of Plant Research, 2013)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Penehyclidine hydrochloride attenuates LPS-induced iNOS production by inhibiting p38 MAPK activation in endothelial cells - Jia Zhan; Zong-ze Zhang; Chang Chen; Kai Chen; Yan-lin Wang (Molecular Biology Reports, 2012)

Hepcidin Treatment Modulates the Expression of Divalent Metal Transporter-1, Ceruloplasmin, and Ferroportin-1 in the Rat Cerebral Cortex and Hippocampus - Lin Li; Christian Holscher; Bing-Bing Chen; Zhi-Feng Zhang; Yue-Ze Liu (Biological Trace Element Research, 2011)

Analysis of influences of spaceflight on chemical constituents in licorice by HPLC–ESI-MS/MS - Jing-Ze Zhang; Wen-Yuan Gao; Ying Gao; Dai-Lin Liu; Lu-Qi Huang (Acta Physiologiae Plantarum, 2011)

Effects of light quality on growth and development of protocorm-like bodies of Dendrobium officinale in vitro - Yuan Lin; Jia Li; Bo Li; Tao He; Ze Chun (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

Heterothallism in Saccharomyces cerevisiae isolates from nature: effect of HO locus on the mode of reproduction - TAL KATZ EZOV; SHANG-LIN CHANG; ZE’EV FRENKEL; AYELLET V. SEGRÈ; MORAN BAHALUL; ANDREW W. MURRAY; JUN-YI LEU; ABRAHAM KOROL; YECHEZKEL KASHI (Molecular Ecology, 2010)

Effects of propofol on pro-inflammatory cytokines and nuclear factor kappaB during polymicrobial sepsis in rats - Xue-Min Song; Yan-Lin Wang; Jian-Guo Li; Cheng-Yao Wang; Qing Zhou; Zong-Ze Zhang; Hui Liang (Molecular Biology Reports, 2009)

Shenfu injection suppresses apoptosis by regulation of Bcl-2 and caspase-3 during hypoxia/reoxygenation in neonatal rat cardiomyocytes in vitro - Yan-lin Wang; Cheng-yao Wang; Ben-jing Zhang; Zong-ze Zhang (Molecular Biology Reports, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Effects of market liberalization on income from sugarcane farming in Guangxi, China - Ze-Lin Qin (Sugar Tech, 2005)